Preventing falls Guidelines for Elderly in Thailand - Popijan, Monrudee; Sonsnam, Wipakon; Maytapattana, Muntanavadee (International Journal of Psychosocial Rehabilitation, 2020)
This paper is based on critically derived new ways and behavioral patterns to prevent fall incidents among Thai elderly. In order to justify this problem statement, online survey-based quantitative research is conducted where randomly five-point Likert scale-based questionnaires are distributed among the professionals of this nursing field, where only 309 of them give the valid outcomes. After implementing the structural equation modeling in statistical analysis, it becomes concluded that there is a significant relationship between the activities performed after fall episode and preventing fall in elderly, and between communication to health technicians of the institution and preventing fall in elderly by considering the moderating role of elderly self-care behavior. This informative research will be an attractive source to upgrade nursing training programs. In addition, there are some limitations regarding the study data collection and its studied population, which can be overcome by upcoming researchers.